2021
DOI: 10.1111/1744-7917.12933
|View full text |Cite
|
Sign up to set email alerts
|

The importance of vitellogenin receptors in the oviposition of the pond wolf spider, Pardosa pseudoannulata

Abstract: Vitellogenin receptor (VgR) is crucial for vitellogenin (Vg) uptake by oocytes. VgR is less known in Arachnida, especially in spiders. Different from only one VgR in an arthropod species, two VgRs, VgR‐1 and VgR‐2, were found in the pond wolf spider, Pardosa pseudoannulata. Both VgRs had the typical domains of the low‐density lipoprotein receptor family except for the absence of the ligand‐binding domain 1 in VgR‐2. Spatiotemporal expression profiles showed that two VgR genes were consistently highly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Vitellogenin (Vg) is the precursor of Vitellin, which provides necessary nutrients for the egg development of arthropods, and vitellogenin receptor (VgR) is the key to the uptake of Vg by oocytes. 46 At the molecular level, the decrease of expression of TcVg and TcVgR in T. cinnabarinus mites was detected at high temperatures. Juvenile hormone (JH) can promote the phosphorylation of VgR for Vg deposition, 47 but the change of JH was not obvious under high-temperature conditions in this experiment, so the change of VgR may be regulated by other genes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Vitellogenin (Vg) is the precursor of Vitellin, which provides necessary nutrients for the egg development of arthropods, and vitellogenin receptor (VgR) is the key to the uptake of Vg by oocytes. 46 At the molecular level, the decrease of expression of TcVg and TcVgR in T. cinnabarinus mites was detected at high temperatures. Juvenile hormone (JH) can promote the phosphorylation of VgR for Vg deposition, 47 but the change of JH was not obvious under high-temperature conditions in this experiment, so the change of VgR may be regulated by other genes.…”
Section: Discussionmentioning
confidence: 94%
“…This research suggested that downregulation of FOXO under high temperatures might result in shortened lifespan of T. cinnabarinus . Vitellogenin (Vg) is the precursor of Vitellin, which provides necessary nutrients for the egg development of arthropods, and vitellogenin receptor (VgR) is the key to the uptake of Vg by oocytes 46 . At the molecular level, the decrease of expression of TcVg and TcVgR in T. cinnabarinus mites was detected at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The ecdysteroid 20-hydroxyecdysone can up-regulate vitellogenin in the Parasteatoda tepidariorum spider ( Bednarek et al, 2019 ). However, the non-viable eggs produced in the ecdysteroid signaling-suppressed P. pseudoannulata females may not be associated with vitellogenesis, as the expression levels of vitellogenin and its receptor are not affected by ecdysteroid application ( Yang et al, 2022 ). Thus, further exploration of the mechanisms underlying non-viable egg production is required.…”
Section: Discussionmentioning
confidence: 99%
“…As a powerful tool for gene function studies, dsRNA-mediated silencing or inhibition of target genes has been widely used in various arthropods [ 67 ]. There were also studies using RNAi to silence in P. pseudoannulata [ 68 , 69 ]. Therefore, we performed RNAi experiments by injecting dsRNA into P. pseudoannulata to determine the effect of silencing HSP genes on the heat tolerance of P. pseudoannulata .…”
Section: Discussionmentioning
confidence: 99%